PERSEPSI MASYARAKAT TERHADAP PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN PASCA PEMEKARAN DI KECAMATAN UNGARAN BARAT TAHUN 2017 - Ardik Ardiansyah; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2017)
Administration of population is one form of public service that must be held by the Local Government related to basic services of life. Subdistrict as government agencies, are required to provide excellent service (one of which is the settlement administration services) to the public. Good public services can be achieved if accompanied by an excellent resource officers. The aim of research to find out the perception of public perceptions of public services, especially in the field of population administration at the district office Ungaran Barat, Semarang regency in 2017. Efforts to address concerns and objectives of research carried out using public service indicators that have been developed by Zeithemal, Parasuraman & Berry consisting of tangibles, relibility, responsiveness, competence, courtesy, credibility, security, access, communication, and understanding the costumers. This research uses descriptive quantitative research methods, which dianalisisa and presented in tabular form and processed using SPSS program for the data to be valid.The population in this study is the community sub-district of West Ungaran. While the sample is most people who use the District of West Ungaran public services in the field of population administration drawn at random (accident sampling) and numbered as many as 100 people. The results showed that the public service field of population administration at the district office Ungaran Barat largely rated by the community. People are already satisfied with the performance Ungaran Barat district office employees. But the need to improve services so that excellent service can always be realized. Keywords: Public Services; Population administration